Aktivitas Antibakteri Ekstrak Kelopak Bunga Rosella Terenkapsulasi Maltodekstrin dan Sinergitasnya dengan Isoniazida dan Rifampisin Terhadap Mycobacterium tuberculosis H37rv: Antibacterial Activity of Rosella Calyx Extract Encapsulated by Maltodextrin and Its Sinergity with Isoniazid and Rifampicin Against Mycobacterium tuberculosis H37rv - N. Djide, Nana Juniarti; Djide, M.Natsir; Amir, Muhammad Nur; Sartini, Sartini (Universitas Tadulako, 2019)
First-line drugs (Isoniazid and Rifampicin) for the treatment of tuberculosis are known to have experienced resistance to Mycobacterium tuberculosis. The aim of this study was to determine the minimum inhibitory concentration (MIC) of maltodextrin encapsulated rosella calyx extract and its ability to provide a synergistic effect with Isoniazid (INH) and Rifampicin (RIF) on M. tuberculosis R37rv. Rosella calyxs were macerated using 50% ethanol and encapsulated using maltodextrin. Antibacterial activity was carried out by determining MIC value using Microscopic Observation and Direct Susceptibility (MODS) method. The synergistic effect was carried out by calculating the Fractional Inhibition Concentration Index (FICI). The results showed that this extract was able to inhibit M. tuberculosis H37rv with MIC of 10 mg/ ml. The FICI value of the combination of extract with INH and rifampicin was obtained 1.25. This showed that rosella calyx extract is not synergistic with INH and rifampicin, might be due to rosella calyx extract has an antibacterial effect with a different mechanism with INH and Rifampicin.